Impact of Dual-Energy Computed Tomography (DECT) Postprocessing Protocols in Detection of Monosodium Urate (MSU) Deposits in Foot Tendons of Cadavers - Klauser, Andrea Sabine; Strobl, Sylvia; Schwabl, Christoph; Kremser, Christian; Klotz, Werner; Vasilevska Nikodinovska, Violeta; Stofferin, Hannes; Scharll, Yannick; Halpern, Ethan (MDPI AG, 2023)
Objective: To evaluate two different DECT postprocessing protocols for detection of MSU deposits in foot tendons of cadavers with verification by polarizing light microscopy as gold standard. Material and Methods: A total of 40 embalmed cadavers (15 male; 25 female; median age, 82 years; mean, 80 years; range, 52 - 99; SD ± 10.9) underwent DECT to assess MSU deposits in foot tendons. Two postprocessing DECT protocols with different Hounsfield unit (HU) thresholds 150/500 (=established) versus 120/500 (= modified) HU were applied to dual source acquisition with 80 kV for tube A and 140 kV for tube B. Six fresh cadavers (4 male; 2 female; median age, 78; mean, 78,5; range 61 - 95 ) were examined by DECT. Tendon dissection of 2/6 fresh cadavers with positive DECT 120 and negative DECT 150 studies were used to verify MSU deposits by polarizing light microscopy. Results: The tibialis anterior tendon was found positive in 57.5%/100% (DECT 150/120), peroneus tendon in 35%/100%, achilles tendon in 25%/90%, flexor halluces longus tendon in 10%/100%, and tibialis posterior tendon in 12.5%/97.5%. DECT 120 resulted in increased tendon MSU deposit detection, when DECT 150 was negative, with an overall agreement between DECT 150 and DECT 120 of 80 % (P = 0.013). Polarizing light microscope confirmed MSU deposits detected only by DECT 120 in tibialis anterior, achilles, flexor halluces longus and peroneal tendons. Conclusion: The DECT 120 protocol showed a higher sensitivity when compared to DECT 150.
Keywords: Dual-energy computed tomography; gout; tendon; foot; monosodium urate deposits